Exercise-induced hypothalamic neuroplasticity: Implications for energy and glucose metabolism - Eunsang Hwang; Bryan Portillo; Kyle Grose; Teppei Fujikawa; Kevin W. Williams (Elsevier, 2023)
Background: Neuroplasticity refers to the brain's ability to undergo functional and structural changes in response to diverse challenges. Converging evidence supports the notion that exercise serves as a metabolic challenge, triggering the release of multiple factors both in the periphery and within the brain. These factors actively contribute to plasticity in the brain, and in turn, regulate energy and glucose metabolism. Scope of Review: The primary focus of this review is to explore the impact of exercise-induced plasticity in the brain on metabolic homeostasis, with an emphasis on the role of the hypothalamus in this process. Additionally, the review provides an overview of various factors induced by exercise that contribute to energy balance and glucose metabolism. Notably, these factors exert their effects, at least in part, through actions within the hypothalamus and more broadly in the central nervous system. Major Conclusions: Exercise elicits both transient and sustained changes in metabolism, accompanied by changes in neural activity within specific brain regions. Importantly, the contribution of exercise-induced plasticity and the underlying mechanisms by which neuroplasticity influences the effects of exercise are not well understood. Recent work has begun to overcome this gap in knowledge by examining the complex interactions of exercise-induced factors which alter neural circuit properties to influence metabolism.